Apigenin promotes remodeling of peripheral and skeletal adipocytes in response to β3-AR and TLR4 activation - Okla, Meshail (Frontiers in Endocrinology, 2025)
BackgroundInflammation impairs adipocyte browning and diminishes the protective role of adaptive thermogenesis against obesity and metabolic disorders. The aim of this study is to evaluate the effects of the anti-inflammatory dietary compound apigenin (Api) on adaptive thermogenesis in C57BL/6 mice in the presence of inflammation and to determine whether changes occur in skeletal adipocytes in these mice.MethodsLipopolysaccharide (LPS) was administered intraperitoneally at 8 µg/mouse every other day for 2 weeks to activate TLR4 signaling. Api was administered intraperitoneally at 30 mg/kg every other day for 2 weeks. To stimulate thermogenesis, CL316,243 (CL), a β3-adrenergic receptor agonist, was administered at 1 mg/kg during the final 5 days. Accordingly, four experimental groups were created: control, CL, LPS+CL, and Api+LPS+CL.ResultsOur results show that Api restored CL-induced thermogenesis in LPS-injected mice. This effect was mediated by inguinal white adipose tissue (iWAT) browning, accompanied by reduced inflammation and alterations in genes involved in fatty acid oxidation and de novo lipogenesis. The thermogenic effect of Api was specific to iWAT and was not observed in brown adipose tissue or visceral fat. Notably, these metabolic changes were associated with bone marrow fat expansion, without affecting osteogenic markers or trabecular and cortical bone parameters.ConclusionsCollectively, Api positively regulates thermogenesis and lipid metabolism in iWAT of LPS-injected mice and promotes lipid accumulation in the bone marrow without causing perturbations in bone parameters. Therefore, Api holds promise for restoring thermogenesis under inflammatory conditions. However, further investigation is needed to elucidate the impact of Api-induced adipose tissue remodeling on skeletal health, particularly under conditions of prolonged supplementation.